Effect of individualized worksite exercise training on aerobic capacity and muscle strength among construction workers - a randomized controlled intervention study - Bibi Gram; Andreas Holtermann; Karen Søgaard; Gisela Sjøgaard (Nordic Association of Occupational Safety and Health (NOROSH), 2012)
OBJECTIVES: The combination of high physical work demands and low physical capacity has been shown to increase the risk for cardiovascular disease and musculoskeletal disorders. The aim of this study was to assess the physical capacity of construction workers and evaluate the effect of individually tailored exercise programs on their physical fitness and muscular capacity. METHOD: The study was a randomized controlled trial of male constructions workers allocated to either an exercise or control group. The intervention lasted 12 weeks, and the exercise group trained 3 x 20 minutes a week. The participants completed health checks before and after the intervention period. Data from the first health check were used to tailor the exercise in the interventions. RESULTS: At baseline, participants had maximal oxygen consumption (VO_2max) of 2.9 [standard deviation (SD) 0.7] l/min and body mass index (BMI) of 28.3 (SD 4.7). Compared to representative data on employees in Denmark (N=78), this study population (N=67) had significantly lower relative aerobic capacity [difference in z-score -1.13 , standard error (SE) 0.1, P<0.001] and higher BMI [difference in z-score 1.10, SE 0.2, P<0.001] at baseline. With respect to the intervention, group x time analyses showed a significant difference in estimated change in VO_2max of 0.4 l/min for the exercise group and 0.0 l/min for the control group (P<0.001). Body mass and other general health measures remained unchanged. CONCLUSION: Training for 20 minutes, 3 times a week significantly increased VO_2max with a clinically relevant magnitude regarding risk of cardiometabolic disorders. This study demonstrates a good effectiveness for integrating short exercise bouts into organizational routines among constructions workers.